Performance of P16INK4a immunocytochemical stain in facilitating cytology interpretation of HSIL for HPV-positive women aged 50 and above - Hou, Jun; Du, Hui; Wang, Chun; Song, Fangbin; Qu, Xinfeng; Wu, Ruifang (Frontiers in Oncology, 2024)
Background Few articles have focused on the cytological misinterpretation of high-grade squamous intraepithelial lesion (HSIL). Due to estrogen deficiency, cervical epithelial cells in postmenopausal women tend to show atrophic change that looks like HSIL on Papanicolaou-stained cytology slides, resulting in a higher rate of cytological misinterpretation. P16INK4a immunocytochemical staining (P16 cytology) can effectively differentiate diseased cells from normal atrophic ones with less dependence on cell morphology. Objective To evaluate the role of P16 cytology in differentiating cytology HSIL from benign atrophy in women aged 50 years and above. Methods Included in this analysis were women in a cervical cancer screening project conducted in central China who tested positive for high-risk human papillomavirus (hr-HPV) and returned back for triage with complete data of primary HPV testing, liquid-based cytology (LBC) analysis, P16 immuno-stained cytology interpretation, and pathology diagnosis. The included patients were grouped by age: ≥50 (1,127 cases) and <50 years (1,430 cases). The accuracy of LBC and P16 cytology in the detection of pathology ≥HSIL was compared between the two groups, and the role of P16 immuno-stain in differentiating benign cervical lesions from cytology ≥HSIL was further analyzed. Results One hundred sixty-seven women (14.8%; 167/1,127) in the ≥50 group and 255 (17.8%, 255/1,430) in the <50 group were pathologically diagnosed as HSIL (Path-HSIL). LBC [≥Atypical Squamous Cell Of Undetermined Significance (ASCUS)] and P16 cytology (positive) respectively detected 63.9% (163/255) and 90.2% (230/255) of the Path-≥HSIL cases in the <50 group and 74.3% (124/167) and 93.4% (124/167) of the Path-≥HSIL cases in the ≥50 group. LBC matched with pathology in 105 (41.2%) of the 255 Path-≥HSIL cases in the <50 group and 93 (55.7%) of the 167 Path-≥HSIL cases in the ≥50 group. There were five in the <50 group and 14 in the ≥50 group that were Path-≤LSIL cases, which were interpreted by LBC as HSIL, but negative in P16 cytology. Conclusion P16 cytology facilitates differentiation of Path-≤LSIL from LBC-≥HSIL for women 50 years of age and above. It can be used in the lower-resource areas, where qualified cytologists are insufficient, as the secondary screening test for women aged ≥50 to avoid unnecessary biopsies and misinterpretation of LBC primary or secondary screening.